Neurosurgical emergencies - Loftus, Christopher M. (Thieme Publishers, 2018)
The third edition of this acclaimed book covers frequently encountered neurosurgical emergencies, with contributions from renowned experts in their respective subspecialties. Clinical insights and easy-to-follow protocols are presented for emergencies associated with disease, infection, and trauma - and complications such as status epilepticus and acute shunt malfunction. Injury classification, evaluation, clinical presentation, imaging, surgical indications, approaches, and prognosis are presented for each condition. Concise, evidence-based descriptions enable readers to rapidly gain a solid understanding of the pathogenesis of each problem